The borderlands of education : Latinas in engineering - Camacho, Michelle Madsen, 1969- (Lexington Books, a wholly owned subsidiary of The Rowman & Littlefield Publishing Group, Inc., 2013)
Why are there so few Latina engineers and what is the potential for change given demographic shifts of the Latino population? This interdisciplinary, mixed-methods approach offers a new paradigm for examining the crisis of Latinas in engineering (a field that remains 82% male), illuminating the nuanced and multiple exclusionary forces that shape the culture of engineering and its borderlands.